The validity of the renal Doppler resistivity index in renal allograft infections - Moataz Fatthy; Karim M. Soliman; Éva Csongrádi; Abd El Rahman Marzouk; Ahmed Fathy; Ahmed Fayed (Renal Failure)
Background The correlations between the intra-renal resistive index (RRI) and renal histopathology characteristics, especially in those with infected allografts, have not been sufficiently investigated in renal transplant recipients. We aimed to examine the correlation between RRI and renal allograft infection in these subjects.Methods One hundred nine renal allograft recipients were recruited, and RRI was evaluated for correlation with renal allograft infection. Based on laboratory and histopathological findings, 64 renal-allograft recipients were recruited for the infected group, and 45 were recruited for the non-infected group.Results The causes of allograft infection were Cytomegalovirus (CMV) infection (30.3%), urinary tract infections (UTI) (18.3%), and polyomavirus 1 (BK virus) infections (10.1%). There was a statistically significant difference in RRI in those with allograft infections, with the ROC curve for detection of infection utilizing RRI demonstrated an Area Under Curve 0.634 (p-value 0.015; cutoff value: 0.765; CI:0.527–0.742), with a specificity of 64.4% and a sensitivity of 68.8%.Conclusion Normal renal graft arterial resistivity index values, despite a renal allograft dysfunction, may be indicative of allograft infection, guiding clinicians’ decisions regarding kidney biopsy and facilitating further biopsy interpretations.